Quality Traits of Fillet of Gilthead Sea Bream (Sparus aurata L.) of Two Market Sizes Reared according to an “Antibiotic-Free” Approach - A. Roncarati; M. C. T. Meligrana; F. Laus; A. Spaterna (Journal of Food Quality)
Rearing of “antibiotic-free” fish is becoming one of the most important goals to be achieved in the near future. Strategies are going to be adopted to increase nonspecific immune system and biosecurity in fish farming. To show the quality traits of gilthead sea breams reared under a prescription of “antibiotic-free” (ABF), two different market sizes (R: about 350 g and M: about 490 g) were analysed at the end of the farming cycle performed in a floating cage plant in the Adriatic sea, in the Gulf of Valona (Albania). Proximate composition and fatty acid profile were determined in April and June 2018. The omega-3 content demonstrated that the ABF samples collected according to the fish size and the harvest month can be defined as “rich in omega-3,” in compliance with the Annex to the Regulation (EC) n. 1924/2006, with a trend to increase in relation to fish growth.